Influence of Endocavitating Rotary Cavitator Parameters on Cavitation Effect - HAN Guihua; ZHU Yipeng; HONG Jian; LI Dawei (Journal of Harbin University of Science and Technology, 2024)
In this paper，the numerical simulation of the rotary cavitator with internal bore using Fluent software was carried out by the control variable method，and the influence law of structural parameters ( bore diameter and depth of blind bore，number of single row of blind bore) and operating parameters ( rotational speed and inlet pressure) on the cavitation effect was obtained: the increase of bore diameter，bore depth and number of single row of blind bore of rotor，and the increase of rotational speed ( 2 000 ～3 000 r / min) ， the volume of gas in the blind bore If the inlet pressure ( 1 MPa～4 MPa) increases，the volume of gas in the blind bores decreases. The temperature rise and conductivity changes of the cavitation process of pure water samples were used as the cavitation effect test criteria，and the temperature rise and conductivity increased significantly with the increase of rotational speed from 3 000 ～9 000 r / min to indirectly verify the results of numerical simulation. This paper provides a reference for the optimization of the structural parameters of the endocavitating rotary cavitator.